Elastiease: Wasting Less and Smiling More—A Clinical Innovation - Prajwal Prabhu; M Hemanth; Afshan S. Waremani; M Aravind; B R Kavya; Rakshitha Raj (Journal of Pharmacy and Bioallied Sciences)
Introduction: Sustainability in orthodontics is gaining prominence as the field seeks eco-friendly alternatives to conventional practices. Materials and methods: This paper presents an innovative device designed to aid in the placement of orthodontic elastics, crafted entirely from commonly discarded clinical materials—unused portions of elastomeric modules and stainless steel rectangular wire. By repurposing these materials, the device not only addresses the practical challenge of elastic placement but also exemplifies the “best out of waste” concept, promoting resource efficiency and waste reduction. Conclusion: This sustainable approach supports greener clinical practices while enhancing patient compliance, offering a simple yet impactful step toward environmentally responsible orthodontic care.cal systems.